(3OjhGf GdHMJQjs - (3GdHMJQj , CHh YHGOI GdhdjO Hf YHjO Hf jMji GdWGFj GdHMJQj, GdHMJQj,J (B284 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje CoJQGc JSeoY ddMeGe GdfUa TLhG jchf cTLhc GdeSJWQa s
(3BNQgG (B:s
(3eJi JSCd GdSLRi Yf YjH NGdJj jHqjf dc GdSLRi eG cGf NGajkG aOGA dg eSJfHWC GdfLM CNOLJ ehGYjOg MJi QLYf CeGfjG s
(3fSNI KGdKIs
(3hQO CjVkG JMJ Qbe (B"475(3,(B667(3,(B917(3,(B2176(3,(B2191(3,(B2204(3,(B2347"s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B9 - (3U (B141s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B38 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B779s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs